Developing Science Gateways for Drug Discovery in a Grid Environment - Pérez‑Sánchez, Horacio; Rezaei, Vahid; Mezhuyev, Vitaliy; Man, Duhu; Peña‑García, Jorge; Den‑Haan, Helena; Gesing, Sandra (Springer, 2016)
Methods for in silico screening of large databases of molecules increasingly complement and replace experimental techniques to discover novel compounds to combat diseases. As these techniques become more complex and computationally costly we are faced with an increasing problem to provide the research community of life sciences with a convenient tool for high-throughput virtual screening on distributed computing resources.